2003
DOI: 10.1097/00061198-200310000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Compliance Barriers in Glaucoma: A Systematic Classification

Abstract: Significant barriers to compliance exist for patients with glaucoma in addition to those cited by previous ophthalmic studies. A systematic classification (i.e., taxonomy) of these barriers was formulated to assist in optimizing patient education and problem-solving regarding prescribed therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
258
1
13

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(279 citation statements)
references
References 14 publications
7
258
1
13
Order By: Relevance
“…Both travoprost and timolol are available in BAK-free formulations in some parts of the world (travoprost Z (Alcon Laboratories) and timolol maleate in preservative-free single-dose vials by various manufacturers); however, a multi-bottle regimen is more complex and less convenient than fixed combination therapy, and may be associated with reduced therapeutic compliance. 33 Thus, there is a need for a BAK-free fixed combination IOP-lowering product so that patients requiring more than a single agent for IOP control can be managed medically without chronic exposure to BAK.…”
Section: Discussionmentioning
confidence: 99%
“…Both travoprost and timolol are available in BAK-free formulations in some parts of the world (travoprost Z (Alcon Laboratories) and timolol maleate in preservative-free single-dose vials by various manufacturers); however, a multi-bottle regimen is more complex and less convenient than fixed combination therapy, and may be associated with reduced therapeutic compliance. 33 Thus, there is a need for a BAK-free fixed combination IOP-lowering product so that patients requiring more than a single agent for IOP control can be managed medically without chronic exposure to BAK.…”
Section: Discussionmentioning
confidence: 99%
“…23 We modified the scale to be appropriate for glaucoma patients and eye drop use with input from four practicing ophthalmologists, 10 glaucoma patients taking glaucoma eye drops, the peer-reviewed literature, and results from our earlier work, 31 in which we asked over 300 glaucoma patients from four practices about their problems and concerns in using their glaucoma medications. [32][33][34][35] The main changes that were made to the medication self-efficacy scale in hypertensive patients scale were that the questions asking about specific side effects to anti-hypertensive medications were modified to reflect specific side effects of glaucoma medications. Also, we added a series of questions focusing on ability to use eye drops correctly.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…For some patients this includes multiple medications instilled several times per day. Previous studies have shown that patients commonly miss eye drop doses [1][2][3][4][5][6] and that poor adherence is associated with more severe visual field loss. 7 Kass et al, 1 using an electronic dose monitor, found that 62% of patients omitted 10% of doses and 15% of patients omitted 50% of doses.…”
Section: Introductionmentioning
confidence: 99%